Чудовищ.net: [роман] / Наталья Тимошенко, Лена Обухова - Тимошенко Наталья Васильевна (Секретное досье, 2019)
Экземпляры: ф.18 (2021) / Инвентарный номер: 56816 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 41 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6